The potential feasibility of mangrove crab (Scylla serrata) silvofishery aquaculture (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rinaldy H, Iskandar J, Cahyandito MF, Sunardi. 2023. The potential feasibility of mangrove crab (Scylla serrata) silvofishery aquaculture. Biodiversitas 24: 3344-3354. The degradation of mangrove forests in Indonesia has reached more than 50%, and increases continuously. Sei Beduk is one of the Sub-districts in Batam City, Indonesia, that has mangrove forest damage where the density of trees per hectare is below the normal value of
Keywords: Ecosystem Approach to Fisheries Management (EAFM), Silvofishery Aquaculture, Batam.